2018
DOI: 10.1093/scan/nsy021
|View full text |Cite
|
Sign up to set email alerts
|

Subjective value representations during effort, probability and time discounting across adulthood

Abstract: Every day, humans make countless decisions that require the integration of information about potential benefits (i.e. rewards) with other decision features (i.e. effort required, probability of an outcome or time delays). Here, we examine the overlap and dissociation of behavioral preferences and neural representations of subjective value in the context of three different decision features (physical effort, probability and time delays) in a healthy adult life span sample. While undergoing functional neuroimagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
92
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 81 publications
(112 citation statements)
references
References 63 publications
(104 reference statements)
12
92
2
2
Order By: Relevance
“…Both data sets (Study 1 and Study 2) were collected as part of large‐scale multimodal neuroimaging projects focused on decision making. Subsets of the Study 1 behavioral (Seaman et al, ), fMRI (Seaman et al, ) and PET (Dang et al, ; Dang et al, ; Smith et al, ) data were previously included in other publications. Specifically, age effects on D2‐like BP ND in a subset of Study 1 participants were reported or noted in three previous publications (Dang et al, ; Dang et al, ; Smith et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both data sets (Study 1 and Study 2) were collected as part of large‐scale multimodal neuroimaging projects focused on decision making. Subsets of the Study 1 behavioral (Seaman et al, ), fMRI (Seaman et al, ) and PET (Dang et al, ; Dang et al, ; Smith et al, ) data were previously included in other publications. Specifically, age effects on D2‐like BP ND in a subset of Study 1 participants were reported or noted in three previous publications (Dang et al, ; Dang et al, ; Smith et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Both data sets (Study 1 and Study 2) were collected as part of largescale multimodal neuroimaging projects focused on decision making. (Seaman et al, 2016), fMRI (Seaman et al, 2018) and PET (Dang et al, 2016;Dang et al, 2017;Smith et al, 2017) data were previously included in other publications.…”
Section: Methodsmentioning
confidence: 99%
“…We acknowledge that there are other integrative processes (e.g., subjective valuation across choice options). These processes, however, do not seem to be affected by aging (Seaman et al, 2018) and thus were less informative for our reflection about social decision making and aging in the context of CISDA.…”
Section: Remaining Challenges For Cisda In Improving Our Understandmentioning
confidence: 96%
“…We acknowledge, that other nonsocial factors (outcomes delays, risk, decision effort; Seaman et al, 2018) may also affect subjective value integration in social decision making. We contend, however, that theory of mind, emotion regulation, and memory for past experience represent key processes that impact value integration in aging because they predict social decision-making quality (Tabibnia et al, 2008;Beadle et al, 2012;Rilling & Sanfey, 2011) and change over the aging process (Mather, 2016;Ebner et al, 2016;Scheibe & Carstensen, 2010;Agarwal, Driscoll, Gabaix, & Laibson, 2009).…”
Section: Theory Of Mindmentioning
confidence: 99%
“…It is presently unclear if aging systematically affects discounting of future rewards despite a plethora of research on the topic. Some studies have reported reduced discounting with older age (Green, Fry, & Myerson, 1994;Green, Myerson, & Ostaszewski, 1999;Eppinger, Nystrom, & Cohen, 2012;Halfmann, Hedgcock, & Denburg, 2013;Harrison, Lau, & Williams, 2002;Jimura et al, 2011;Li et al, 2013;Löckenhoff et al, 2011;Reimers, Maylor, Stewart, & Chater, 2009;Simon et al, 2010;Sparrow & Spaniol, 2018), others find increased discounting (Read & Read, 2004;Seaman et al, 2016;Seaman et al, 2018), and some report no age differences (Chao, Szrek, Pereira, & Pauly, 2009;Eppinger, Heekeren, & Li, 2018;Green, Myerson, Lichtman, Rosen, & Fry, 1996;Han et al, 2013;Jimura et al, 2011;Rieger & Mata, 2013;Roalf, Mitchell, Harbaugh, & Janowsky, 2011;Samanez-Larkin, Wagner, & Knutson, 2011;Sasse, Peters, & Brassen 2017;Seaman et al, 2016;Sparrow & Spaniol, 2018;Whelan & McHugh, 2009) or nonlinear effects (Richter & Mata, 2018). Some, but not all, discrepancies may be explained by older adults' preferences for specific reward types (e.g., Jimura et al, 2011;Seaman et al, 2016).…”
Section: Intertemporal Decisionsmentioning
confidence: 99%